African swine fever How it occurs and how to control? - Biswal, Prachurya; Bharti, P K; Somagond, Arun; Panda, Snehasmita; Yadav, Seema; Harini, K R; Sriranga, K R (Indian Farming, 2021)
The continued spread of ASFV in many Countries demonstrates a potential for further spread in other regions of the World. There are still many gaps in our knowledge of the biology of ASFV, its interaction with hosts, immune responses correlating with protection and how these can be activated. Vaccine development against ASF has been hampered by large gaps in knowledge concerning ASFV infection and immunity. Current studies indicate that ASFV isolates circulating in Eastern Europe and the Russian Federation are highly virulent and kill most of the infected domestic pigs and wild boars. There is a need for continued monitoring in the field, along with experimental infections, to identify ASFV isolates of altered virulence.